High-toughness PPA material and preparation method thereof
By using high relative molecular weight PPA resin matrix, special structure toughening agent, montmorillonite and polytetrafluoroethylene oligomer in PPA materials, combined with a rigorous preparation process, the existing PPA materials are solved, and the problems of softening, deformation, insufficient heat resistance, poor toughness and limited chemical corrosion resistance at high temperatures are achieved, and the material's heat resistance, toughness and chemical resistance are significantly improved.
Patent Information
- Application Number
- CN202510014859.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
Smart Images

Figure CN119798988A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PPA materials, and in particular to a high-toughness PPA material and a preparation method thereof. Background Art
[0002] In today's era of rapid technological development, many high-end manufacturing fields have increasingly stringent requirements for material performance. Take automobile manufacturing as an example. The peripheral parts of the engine must not only withstand high temperatures and be in a harsh thermal environment of 150℃-200℃ for a long time, but also need to deal with frequent vibrations and shocks; precision structural parts in the electronic and electrical industry are also faced with high temperatures generated by heat dissipation and complex external forces. Although traditional PPA materials have basic mechanical properties, heat resistance and chemical resistance to a certain extent, they can no longer meet the growing needs of these cutting-edge fields.
[0003] Existing PPA materials are prone to softening and deformation at high temperatures, and their heat resistance is insufficient, which shortens the life of automotive engine components and increases the risk of electronic and electrical failures. When subjected to external impact, they lack toughness and are prone to breakage, making it impossible to ensure the long-term reliable operation of the product. Moreover, when faced with chemical environments or corrosive substances that electronic components may come into contact with, their resistance to chemical corrosion is limited and the material structure is easily damaged.
[0004] Therefore, it is urgent to invent a high-toughness PPA material and its preparation method. By carefully selecting raw materials, using toughening agents with special structures, high-performance heat-resistant additives and chemical-resistant additives, and designing a rigorous preparation process, strictly controlling each link from pretreatment to extrusion molding, the heat resistance of the PPA material can be improved, and the thermal decomposition temperature can be significantly increased; the toughness can be enhanced to effectively buffer the impact of external forces; the chemical resistance can be strengthened to resist various corrosive media, thereby providing solid and reliable material support for high-end manufacturing and promoting industry development. Summary of the invention
[0005] Technical issues solved
[0006] In view of the deficiencies in the prior art, the present invention provides a high-toughness PPA material and a preparation method thereof.
[0007] Technical Solution
[0008] To achieve the above-mentioned solution, the present invention provides the following technical solutions: a high-toughness PPA material, the raw materials of which include a PPA resin matrix, a toughening agent, a compatibilizer, a heat-resistant additive and a chemical-resistant additive, the PPA resin matrix accounts for 57% to 59%, the toughening agent accounts for 16% to 18%, the compatibilizer accounts for 12% to 14%, the heat-resistant additive accounts for 12% to 14%, and the chemical-resistant additive accounts for 6% to 8%.
[0009] Preferably, the PPA resin matrix selects a PPA resin with a high relative molecular mass as a base material.
[0010] Preferably, the toughening agent is selected from rubber particles with polybutadiene as the core and styrene-acrylonitrile copolymer as the shell.
[0011] Preferably, the compatibilizer is maleic anhydride grafted PPA.
[0012] Preferably, the heat-resistant additive is montmorillonite.
[0013] Preferably, the chemical resistance additive is polytetrafluoroethylene oligomer.
[0014] A method for preparing a high-toughness PPA material comprises the following steps:
[0015] Step 1: Preprocessing
[0016] Dry each raw material in a precisely controlled temperature vacuum oven according to its own characteristics: PPA resin 120℃, 4-6 hours; toughening agent 80℃, 3-4 hours; compatibilizer 90℃, 3-5 hours; montmorillonite 150℃, 2-4 hours; polytetrafluoroethylene oligomer 100℃, 3-4 hours;
[0017] Step 2: Premixing
[0018] Weigh the dry raw materials according to the predetermined ratio using a high-precision electronic scale, stir at a low speed of 500-800 r / min for 3-5 minutes, and then stir at a high speed of 1200-1500 r / min for 5-8 minutes to form a premix;
[0019] Step 3: Melt Blending
[0020] The premix is transferred to a twin-screw extruder, and the temperature of each section of the extruder is set at 280-340°C and the screw speed is set at 200-300 r / min according to the material properties, and melt blended to obtain a melt;
[0021] Step 4: Extrusion
[0022] The melt is extruded through the die head, cooled by either water or air, accurately matched with the traction speed, and pelletized by high-precision tools.
[0023] Preferably, during extrusion molding, the melt obtained by melt blending carries the application potential of the material. After being extruded through the die head, it quickly enters fine processes such as cooling, traction, and pelletizing. The cooling method is selected according to actual production needs and product characteristics. When pursuing efficient cooling, water cooling is appropriate, and the water flow rate is controlled at 0.5-1.0 m / s. When focusing on gentle cooling effect, air cooling is appropriate, and the air cooling wind speed is controlled at 2-5 m / s.
[0024] Preferably, the pulling speed is accurately matched according to the extrusion speed in real time and dynamically, and the error range is strictly controlled within ±5%. A high-precision speed sensor and control system are equipped to monitor and adjust the pulling speed in real time.
[0025] Beneficial Effects
[0026] Compared with the prior art, the present invention provides a high-toughness PPA material and a preparation method thereof, which has the following beneficial effects:
[0027] 1. This high-toughness PPA material has both high strength and high toughness in terms of mechanical properties. It has good tensile strength and can withstand large external forces. It has excellent elongation at break and impact strength, can effectively buffer impacts, and is suitable for complex stress environments, such as parts surrounding automobile engines. It can withstand long-term vibration and impact, has excellent heat resistance, high thermal decomposition temperature, and a stable structure under high temperature conditions. It does not deform when electronic appliances are running and generating heat, ensuring the normal operation of the equipment. It has strong resistance to chemical corrosion and its internal structure is intact in the face of strong acid and alkali media. It can be used in chemical-related scenarios to extend its service life and broaden the application field of the material.
[0028] 2. The preparation method of the high-toughness PPA material is to accurately remove moisture and impurities from the raw materials through pretreatment to avoid problems such as hydrolysis, thus laying a solid foundation for subsequent processing and ensuring stable material performance. The pre-mixing speed and time are precisely controlled to evenly disperse the raw materials and fully contact and fuse the various components to ensure the consistency of the finished product quality. The melt blending is set to control the temperature and speed according to the material characteristics, so that the additives can be perfectly integrated into the PPA matrix, synergistically enhancing the overall performance. The extrusion molding process flexibly selects cooling, accurately matches traction, and precisely cuts the pellets to ensure that the pellets are regular, which is beneficial to subsequent molding and processing, reduces the scrap rate, and improves production efficiency and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the architecture of the present invention;
[0030] Figure 2 It is a schematic diagram of the preparation method of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] See also Figure 1-2 The present invention provides a high-toughness PPA material and a preparation method thereof.
[0033] 1. Raw material selection
[0034] (I) PPA resin matrix
[0035] The PPA resin with high relative molecular mass is selected as the base material. This resin has a unique and regular polymer chain structure, which can give it considerable basic mechanical properties in the initial stage of the material, laying a solid foundation for the subsequent modification process. From the molecular structure level, its regularity ensures that the molecular structure of the material can remain stable in a high temperature environment, ensuring that the material has good heat resistance and effectively resists the destructive effect of high temperature on the material structure.
[0036] (ii) Toughening agent
[0037] Rubber particles with polybutadiene as the core and styrene-acrylonitrile copolymer as the shell are selected as the toughening agent. The core polybutadiene has excellent elastic deformation ability. When the material is subjected to external impact, it can quickly absorb and buffer the impact energy, effectively disperse stress concentration, and avoid material breakage due to excessive local stress. The styrene-acrylonitrile copolymer of the shell has good interface compatibility with the PPA resin matrix. The two are closely combined, which promotes the uniform transmission of stress inside the material. While improving the toughness, it can effectively maintain the rigidity of the material, avoid the transitional reduction of rigidity due to toughening, and ensure the balance of the overall mechanical properties of the material.
[0038] (III) Compatibilizer
[0039] Maleic anhydride grafted PPA is used as a compatibilizer. Its molecular structure carries unique chemically active groups, which can improve the interfacial compatibility between the toughening agent and the PPA resin matrix in a targeted manner. Through chemical bonding and other mechanisms, the two are closely interwoven to form a stable and efficient blending system, which ensures the stability of the material's comprehensive performance while improving the material's toughness. In addition, during the material processing and molding process, such as extrusion and injection molding, the compatibilizer can optimize the rheological properties of the material, improve processing fluidity, reduce processing difficulty and cost, and improve production efficiency.
[0040] (IV) Heat-resistant additives
[0041] Montmorillonite is used as a heat-resistant additive. Montmorillonite has a natural layered nanostructure, and this unique structure gives it extraordinary thermal stability. Under high temperature conditions, the internal structure of montmorillonite is stable. When evenly dispersed in the PPA matrix, its interlayer structure can effectively block the rapid conduction of heat, forming a similar effect to a heat insulation barrier, delaying the penetration of heat into the material. At the same time, with its microstructural characteristics, it can optimize the heat conduction path, guide the even dissipation of heat, help the material break through the heat resistance bottleneck, and meet the use requirements under high temperature conditions.
[0042] (V) Chemical resistance additives
[0043] Polytetrafluoroethylene oligomer is selected as a chemical resistance additive. Its special fluorocarbon chemical bond shows super strong chemical inertness. In the PPA material system, it can be closely arranged on the surface of the material to quickly form a protective film. When the material is exposed to corrosive media such as strong acids and alkalis, the protective film can effectively resist the penetration and erosion of chemical substances by virtue of its own chemical inertness, ensuring the integrity of the fine structure inside the material, and does not affect the other excellent properties of the material during the protection process, ensuring the normal use of the material in a corrosive environment.
[0044] 2. Preparation method
[0045] (I) Pretreatment
[0046] Place the PPA resin in a vacuum oven, set the temperature to 120°C, and dry for 4 to 6 hours. Thoroughly remove the moisture hidden inside the resin, because moisture may cause hydrolysis in subsequent processing, resulting in molecular chain breakage and serious damage to the mechanical properties and stability of the material, so it is necessary to ensure sufficient drying.
[0047] The toughening agent is placed in a vacuum oven at 80°C and dried for 3 to 4 hours to ensure that the elasticity and stability of the toughening agent are not affected, maintain its efficient energy absorption and buffering properties, and lay the foundation for the subsequent improvement of material toughness.
[0048] The compatibilizer is dried in an oven at 90° C. for 3 to 5 hours to allow the active groups therein to fully expand, thereby enhancing its coordination effect on the toughening agent and the PPA resin matrix in the subsequent fusion process and promoting the formation of a stable blending system.
[0049] The montmorillonite is dried at 150°C for 2 to 4 hours to remove the adsorbed moisture through high temperature, activating its thermal stability advantage so that it can better play the role of blocking heat conduction after being integrated into the PPA matrix.
[0050] The polytetrafluoroethylene oligomer is dried at 100°C for 3 to 4 hours to ensure that its chemical protection performance is not affected by moisture and to ensure that it can effectively resist chemical erosion after the material is formed.
[0051] (ii) Premixing
[0052] According to the precise predetermined ratio, use a high-precision electronic scale to accurately weigh the various dried raw materials. The accuracy of the electronic scale is controlled within ±0.01g to ensure the accuracy of the raw material ratio, which is crucial to the consistency and stability of the final material performance.
[0053] Carefully place the weighed raw materials into the high-speed mixer and start the pre-mixing process. First, stir steadily at a low speed of 500-800r / min for 3-5 minutes. At this stage, the materials are initially in contact, and gentle stirring allows them to begin to mix evenly and become familiar with each other's characteristics, avoiding material agglomeration or uneven dispersion due to high-speed impact.
[0054] Then increase the speed to 1200-1500r / min. The materials collide violently and disperse deeply under the action of high-speed cyclone. Continue stirring for 5-8 minutes until all components are fully integrated to form a premix with uniform texture and color, creating good conditions for subsequent melt blending.
[0055] (III) Melt Blending
[0056] The premix is carefully transferred to the twin-screw extruder. Based on the thermal properties, rheological properties and other key parameters of the PPA resin, toughening agent, compatibilizer, montmorillonite and polytetrafluoroethylene oligomer, the temperature of each section of the extruder is carefully set. From the hopper to the die area, the temperature gradient is precisely controlled within the range of 280-340°C to ensure that the material can be fully melted during the extrusion process and the additives are evenly dispersed in the PPA resin matrix. For example, the temperature near the hopper end can be set to 280°C to soften the material initially. As the material moves forward, the temperature gradually rises to 340°C at the die head to ensure that the material is completely melted and mixed evenly.
[0057] At the same time, the screw speed is precisely adjusted to 200-300r / min. The lower screw speed helps the material to fully withstand multiple effects such as shearing, extrusion and transportation in the extruder, allowing the molecular chain to break free from its constraints and stretch freely. Tougheners, heat-resistant additives, chemical-resistant additives, etc. can better interweave, penetrate and fuse with the PPA resin matrix, and finally condense into a uniform and stable melt, achieving a qualitative change in material performance.
[0058] (IV) Extrusion molding
[0059] The melt obtained by melt blending carries the potential for material application. After being extruded through the die, it quickly enters fine processes such as cooling, pulling, and pelletizing.
[0060] In the cooling stage, the cooling method can be selected according to the actual production needs and product characteristics. If you pursue efficient cooling, water cooling is appropriate. The water flows around the melt at an appropriate flow rate, and the high specific heat capacity of water quickly takes away the heat, so that the pellets are instantly shaped and the size is regular and uniform. For example, the water flow rate can be controlled at 0.5-1.0m / s to ensure uniform and stable cooling. If you focus on gentle cooling effects, air cooling is a feasible option. The uniform airflow gently passes through to ensure the quality of pellet molding. At this time, the air cooling wind speed should be controlled at 2-5m / s.
[0061] The traction speed is accurately matched to the extrusion speed in real time and dynamically, and the error range is strictly controlled within ±5% to prevent the pellets from being stretched and deformed due to uneven force. This requires high-precision speed sensors and control systems to monitor and adjust the traction speed in real time to ensure the accuracy and stability of the pellet size.
[0062] The pelletizer is equipped with high-precision sharp knives, which fall decisively at the right moment to cut off the melt and ensure that the cross-section of the cut pellets is flat and smooth. The sharpness of the knives should be regularly inspected and maintained to ensure the quality of the incision, provide high-quality raw materials for subsequent processing links, and start a new journey of material application.
[0063] 3. Quality Control and Testing
[0064] 1. Quality Control
[0065] Standardized control of raw materials
[0066] For PPA resin, in view of its high relative molecular mass characteristics, gel permeation chromatography is used to accurately detect its molecular weight distribution, and only batches that meet the preset process requirements are allowed to enter the production line; for toughening agents, compatibilizers, heat-resistant additives and chemical-resistant additives, on the one hand, infrared spectroscopy analysis technology is used to accurately confirm the correctness of their chemical structure, and on the other hand, combined with thermogravimetric analysis, particle size analysis and other testing methods, key indicators such as thermal stability and particle size uniformity are comprehensively verified to eliminate the possibility of unqualified raw materials mixing into the production line.
[0067] Dynamic monitoring of the entire production process
[0068] Precise monitoring of the pretreatment stage: High-precision temperature and humidity sensors are reasonably placed inside the vacuum oven to collect and record in real time and in detail the changes in environmental parameters of various components such as PPA resin and toughening agent during the drying process, and continuously compare them with the preset standard values. Once the parameter deviation is detected to be beyond the allowable range, the alarm system is immediately triggered and the adjustment mechanism is started simultaneously to ensure the consistency of the drying effect of each batch of raw materials and prevent adverse problems such as hydrolysis caused by residual moisture from the source.
[0069] Fine control of the premixing process: The high-speed mixer is equipped with a highly sensitive torque sensor and an accurate speed monitor. Through in-depth analysis of the torque change curve during the material mixing process, the mixing uniformity of each raw material can be accurately determined. Combined with real-time monitoring of the speed stability, it ensures that each raw material strictly follows the predetermined low-speed and high-speed mixing process to be fully integrated, and finally forms a premix with uniform texture and stable performance.
[0070] Monitoring of key process parameters of melt blending: Temperature sensors, pressure sensors and professional melt rheometers are scientifically deployed in each key section of the twin-screw extruder. The temperature sensor strictly controls the temperature gradient of 280-340℃ to ensure that the material is fully melted in a suitable thermal environment; the pressure sensor monitors the extrusion pressure of the material in real time, providing a key basis for process adjustment; the melt rheometer focuses on the dynamic detection of material viscosity and fluidity. The three work together to ensure that the additives can be evenly dispersed in the PPA matrix, and the screw speed is always stable in the ideal range of 200-300r / min.
[0071] Monitoring of the extrusion molding process: In the cooling process, if water cooling is used, the water flow rate is precisely controlled with the help of an electromagnetic flowmeter to ensure that the water flows around the melt at a constant and appropriate rate, so that the pellets are instantly and accurately shaped; if air cooling is used, the wind speed is monitored in real time by an anemometer to ensure a uniform and stable cooling rate. The traction device is equipped with a high-precision servo motor, and the encoder is used to feedback the traction speed in real time, which is closely matched with the extrusion speed. The error is strictly controlled within a very small range, effectively preventing the pellets from stretching and deforming; the pelletizer blade is regularly inspected for microscopic wear with the help of an electron microscope to ensure that each cut can make the pellet cross section smooth and flat, providing high-quality raw materials for subsequent processing links.
[0072] (II) Performance testing
[0073] Accurate determination of mechanical properties: Universal material testing machines are used to strictly follow internationally and domestically recognized authoritative standards such as ISO and ASTM to accurately determine the tensile strength, elongation at break, and impact strength of materials. For each production batch, no less than 5 samples are strictly sampled, and each sample is tested 3 times and the average value is taken to ensure the high accuracy of the data, and then further evaluate whether the toughening effect of the material reaches the expected goal.
[0074] Accurate evaluation of heat resistance: Using a thermogravimetric analyzer, the thermal decomposition temperature of the material is tested at a stable heating rate in a selected nitrogen or air atmosphere. Each batch of samples is tested at least twice, and the actual test results are carefully compared with the standard reference values to accurately determine the improvement in heat resistance and clarify the tolerance limit of the material in a high temperature environment.
[0075] Chemical resistance simulation environment test: In order to truly simulate the chemical erosion challenges faced by materials in actual application scenarios, we carefully designed immersion schemes in strong acid and strong alkali solutions of different concentrations based on actual conditions such as contact with automobile engine coolant and the risk of chemical corrosion of electronic appliances. The finished product samples are immersed in them at regular intervals, and after being taken out on time, the mass change is first measured with a high-precision balance, and then the mechanical property attenuation is measured using a universal material testing machine. Through all-round and multi-angle simulation tests, the chemical resistance of the materials is thoroughly examined.
[0076] IV. Design and implementation of controlled trials
[0077] (I) Experimental group settings
[0078] Six groups of tests were set up, and each group weighed raw materials according to different precise predetermined proportions. The specific proportion settings are shown in Table 1. The changes in the proportions of each component are intended to explore the influence of the proportions on the comprehensive properties of the material. For example, the adjustment of the proportion of the toughening agent focuses on the toughness improvement effect, the changes in the proportions of heat-resistant and chemical-resistant additives focus on the corresponding performance enhancement degree, and the changes in the proportion of the compatibilizer examine the effect on the system stability and processing performance.
[0079] Table 1: Precise proportions of raw materials for the six groups of experiments
[0080]
[0081] (II) Preparation process
[0082] Each group of experiments strictly follows the unified preparation process:
[0083] Pretreatment: Dry each raw material in a precisely controlled temperature vacuum oven according to its own characteristics: PPA resin at 120°C for 4 to 6 hours; toughening agent at 80°C for 3 to 4 hours; compatibilizer at 90°C for 3 to 5 hours; montmorillonite at 150°C for 2 to 4 hours; polytetrafluoroethylene oligomer at 100°C for 3 to 4 hours.
[0084] Premixing: Weigh the dry raw materials according to the predetermined proportion using a high-precision electronic scale, stir at a low speed of 500-800 r / min for 3-5 minutes, and then stir at a high speed of 1200-1500 r / min for 5-8 minutes to form a premix.
[0085] Melt blending: The premix is transferred to a twin-screw extruder. The temperature of each section of the extruder is set at 280-340°C and the screw speed is set at 200-300 r / min according to the material properties, and the melt is obtained by melt blending.
[0086] Extrusion molding: The melt is extruded through the die head, cooled by water or air, accurately matched with the traction speed, and pelletized by high-precision tools.
[0087] 5. Performance Testing
[0088] (I) Mechanical properties test
[0089] The tensile strength, elongation at break and impact strength were measured using a universal material testing machine in accordance with international and domestic standards. The tensile strength reflects the material's ability to resist stretching, the elongation at break shows the ductility, and the impact strength reflects the impact toughness. The results are shown in Table 2.
[0090] Table 2: Test results of mechanical properties of PPA materials in six groups of tests
[0091] Test group number Tensile strength(MPa) Elongation at break (%) <![CDATA[Impact strength (kJ / m 2 )]]> 1 120 10 15 2 110 15 20 3 125 8 12 4 130 9 14 5 115 12 16 6 105 20 22
[0092] (II) Heat resistance test
[0093] The thermal decomposition temperature was measured using a thermogravimetric analyzer to characterize the improvement in heat resistance and clarify the high temperature tolerance limit. The results are shown in Table 3.
[0094] Table 3: Test results of heat resistance of six groups of PPA materials
[0095]
[0096]
[0097] (III) Chemical resistance test
[0098] The material samples were immersed in strong acid and strong alkali solutions of different concentrations for a specific period of time. High-precision equipment was used to detect mass changes and mechanical property degradation, and the chemical resistance was examined. The results are shown in Table 4.
[0099] Table 4: Test results of chemical resistance of six groups of PPA materials (taking NaOH solution immersion as an example)
[0100] Test group number Quality change rate (%) Tensile strength attenuation rate (%) 1 0.5 10 2 0.8 12 3 0.4 8 4 0.6 9 5 1.0 15 6 0.7 11
[0101] 6. Results Analysis
[0102] (I) Mechanical properties analysis
[0103] Effect of toughening agent: Comparing test groups 1, 2, and 6, as the proportion of toughening agent increases (15% to 20%), the elongation at break and impact strength increase. For example, in test group 2, the elongation at break increases from 10% to 15%, and the impact strength increases from 15 kJ / m 2 Increase to 20kJ / m 2 ; However, the tensile strength is reduced because the toughening agent contains more flexible components and excessive addition weakens the overall rigidity.
[0104] Effect of compatibilizer: In test group 3, the compatibilizer ratio was increased to 15%, and the tensile strength increased to 125MPa. Because better interface bonding helps stress transfer, the material processing fluidity can be improved and the molding is more dense; but the impact strength is reduced to 12kJ / m 2 , or because the compatibilizer partially affects the dispersion of the toughening agent.
[0105] (II) Heat resistance analysis
[0106] Effect of heat-resistant additives: It can be seen from test groups 4 and 5 that the thermal decomposition temperature of test group 4 containing 15% montmorillonite reaches 440°C, which is higher than that of test group 5 (400°C) without heat-resistant additives, indicating that montmorillonite effectively blocks heat, optimizes heat conduction, and improves heat resistance.
[0107] Correlation with other components: Comparing test groups 1, 2, and 6, changing the ratio of toughening agent and compatibilizer within a certain range has little effect on the thermal decomposition temperature, indicating that heat resistance is mainly dominated by heat-resistant additives, and other components do not interfere with the construction of the heat-resistant system under this ratio change.
[0108] (III) Chemical resistance analysis
[0109] Effect of chemical resistance additives: Test group 5 without polytetrafluoroethylene oligomers had a mass change rate of 1.0% and a tensile strength attenuation rate of 15%, which were higher than those of the groups containing additives, such as test group 1 (0.5%, 10%), proving that its protective film has a significant effect in resisting erosion and stabilizing the internal structure.
[0110] Synergistic factors: Overall, the chemical resistance of each test group is also affected by the density of the material. For example, test group 3 has good processing fluidity and dense molding, and its chemical resistance is slightly better. This shows that the synergistic combination of various components not only affects mechanics and heat resistance, but also affects chemical resistance.
[0111] Through six groups of control tests, the key influence of the precise predetermined ratio of raw materials on the performance of PPA materials is clarified. Tougheners improve toughness but affect rigidity, compatibilizers optimize interface bonding and processing, heat-resistant additives lead to heat resistance improvement, and chemical-resistant additives protect against erosion.
[0112] The optimal ratio range of each raw material is as follows:
[0113]
[0114]
[0115] PPA resin can just build a solid foundation for the material in the narrow range of 57% to 59%. With its regular polymer chain structure, it ensures the stability of the molecular structure of the material under high temperature conditions and maintains excellent heat resistance. At the same time, it provides an ideal matrix platform for the uniform dispersion and modification and efficiency enhancement of various subsequent additives.
[0116] The proportion of toughening agent is between 16% and 18%. This range can not only ensure that the inner core polybutadiene can give full play to its advantage of absorbing impact energy, but also make use of the good compatibility of the outer shell styrene-acrylonitrile copolymer and the PPA resin matrix to accurately maintain the rigidity of the material, avoid the imbalance of material rigidity due to excessive addition of toughening agent, and thus ensure the coordination and unity of the overall mechanical properties.
[0117] The compatibilizer ratio is between 12% and 14%. This range can promote the active groups in the compatibilizer to fully interact with the toughening agent and the PPA resin matrix, maximize the improvement of the interfacial compatibility, build a tight and stable blending system, effectively optimize the rheological properties of the material during the processing and molding process, greatly improve the processing fluidity, and reduce the difficulty and cost of molding.
[0118] When the proportion of heat-resistant additives is in the range of 12% to 14%, the unique natural layered nanostructure of montmorillonite can be fully utilized, which can effectively block the rapid conduction of heat and cleverly optimize the heat dissipation path, so that the heat resistance of the material is significantly improved and it can easily cope with high temperature challenges.
[0119] The proportion of chemical-resistant additives is between 6% and 8%. Polytetrafluoroethylene oligomers can be densely and evenly arranged on the surface of the material to form a tough and reliable protective film, which can effectively resist the erosion of corrosive media such as strong acids and alkalis, effectively protect the integrity of the fine structure inside the material, and ensure that it will not have a negative impact on other excellent properties of the material.
[0120] In actual production and application scenarios, according to the special needs of specific products, such as the emphasis on heat resistance and toughness of peripheral components of automobile engines, and the requirements of chemical resistance and processing accuracy of precision structural parts of electronic and electrical appliances, flexible fine-tuning can be done within these optimal proportions, and the proportion of raw materials can be accurately adjusted to optimize the comprehensive performance of the materials and fully meet the stringent requirements of different fields for high-toughness PPA materials.
[0121] In terms of mechanical properties, this PPA material has both high strength and high toughness, good tensile strength, can withstand large external forces, excellent elongation at break and impact strength, can effectively buffer impact, and is suitable for complex stress environments, such as peripheral components of automobile engines. It can withstand long-term vibration and impact, has excellent heat resistance, high thermal decomposition temperature, and stable structure under high temperature conditions. Electronic appliances do not deform when they are running and generating heat, ensuring the normal operation of equipment. It has strong resistance to chemical corrosion and its internal structure is intact in the face of strong acid and alkali media. It can be used in chemical-related scenarios to extend its service life and broaden the application field of the material.
[0122] The preparation method of the PPA material can accurately remove moisture and impurities from the raw materials through pretreatment to avoid problems such as hydrolysis, lay a solid foundation for subsequent processing, ensure stable material performance, finely control the rotation speed and time of premixing to evenly disperse the raw materials and fully contact and fuse the components to ensure the consistency of finished product quality, set the temperature and control the speed of melt blending according to the material characteristics, so that the additives can be perfectly integrated into the PPA matrix, synergistically enhance the overall performance, and flexibly select cooling, accurately match traction, and accurately cut particles in the extrusion molding process to ensure the regularity of the pellets, which is conducive to subsequent molding and processing, reduces the scrap rate, and improves production efficiency and economic benefits.
[0123] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-toughness PPA material, characterized by: The raw materials include PPA resin matrix, toughening agent, compatibilizer, heat-resistant additive and chemical-resistant additive. The PPA resin matrix accounts for 57% to 59%, the toughening agent accounts for 16% to 18%, the compatibilizer accounts for 12% to 14%, the heat-resistant additive accounts for 12% to 14%, and the chemical-resistant additive accounts for 6% to 8%.
2. A high-toughness PPA material according to claim 1, characterized in that: The PPA resin matrix selects a PPA resin with a high relative molecular mass as a basic material.
3. A high-toughness PPA material according to claim 1, characterized in that: The toughening agent is rubber particles with polybutadiene as the core and styrene-acrylonitrile copolymer as the shell.
4. The high-toughness PPA material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted PPA.
5. The high-toughness PPA material according to claim 1, characterized in that: The heat-resistant auxiliary agent is montmorillonite.
6. The high-toughness PPA material according to claim 1, characterized in that: The chemical resistance additive is polytetrafluoroethylene oligomer.
7. The method for preparing a high-toughness PPA material according to claims 1 to 6, characterized in that: The following steps are included: Step 1: Preprocessing Dry each raw material in a precisely controlled temperature vacuum oven according to its own characteristics: PPA resin 120℃, 4-6 hours; toughening agent 80℃, 3-4 hours; compatibilizer 90℃, 3-5 hours; montmorillonite 150℃, 2-4 hours; polytetrafluoroethylene oligomer 100℃, 3-4 hours; Step 2: Premixing Weigh the dry raw materials according to the predetermined ratio using a high-precision electronic scale, stir at a low speed of 500-800 r / min for 3-5 minutes, and then stir at a high speed of 1200-1500 r / min for 5-8 minutes to form a premix; Step 3: Melt Blending The premix is transferred to a twin-screw extruder, and the temperature of each section of the extruder is set at 280-340°C and the screw speed is set at 200-300 r / min according to the material properties, and melt blended to obtain a melt; Step 4: Extrusion The melt is extruded through the die head, cooled by either water or air, accurately matched with the traction speed, and pelletized by high-precision tools.
8. The method for preparing a high-toughness PPA material according to claim 7, characterized in that: During the extrusion molding, the melt obtained by melt blending carries the application potential of the material. After being extruded through the die head, it quickly enters the fine processes such as cooling, pulling, and pelletizing. The cooling method is selected according to the actual production needs and product characteristics. When pursuing efficient cooling, water cooling is appropriate, and the water flow rate is controlled at 0.5-1.0 m / s. When focusing on gentle cooling effect, air cooling is appropriate, and the air cooling wind speed is controlled at 2-5 m / s.
9. The method for preparing a high-toughness PPA material according to claim 7, characterized in that: The pulling speed is accurately matched according to the extrusion speed in real time and dynamically, and the error range is strictly controlled within ±5%. It is equipped with a high-precision speed sensor and control system to monitor and adjust the pulling speed in real time.